Obstacles to activating the sports marketing process in professional football clubs in Alegria - خذايرية , اسامة; مخلفي , رضا (Journal of Sport Science Technology and Physical Activities, 2021)
The study aimed to identify the obstacles to activating the sports marketing process in professional football clubs in Algeria, from the economic and legislative side, from the point of view of the heads of the boards of directors of the professional clubs of the First Professional League, where the descriptive analytical approach was used for this purpose, and the research sample was represented in (15) single selected by comprehensive inventory method, And a questionnaire consisting of (24) phrases in order to sports marketing, in addition to the economic situation of the country, represent the Most important obstacles that prevent the activation of the sports marketing collect data, as it was divided into two axes, and the study came to the conclusion that the weak application of the legal provisions related to process for Professional football clubs. in Alegria